Work Ethic And Strategic Development of Batik Pekalongan Indonesia on Islamic Business Perspective - Muhamad Masrur; Agus Arwani (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
This paper aims to find out how the work ethics of Pekalongan batik entrepreneurs and the business development strategies of Pekalongan batik entrepreneurs from perspective of Islamic business ethics. This study uses a qualitative approach by observations, interviews, and documentation to Muslim entrepreneurs. The results study note that batik entrepreneurs in Pekalongan conduct their business with a high work ethic spirit, nature maintains and develops business, they do business development strategies mostly by Islamic business ethics, both from marketing strategies such as products, prices, distribution of promotions, and sales systems that adapted times, treating employees, still less additional capital that is related to conventional banking, and still a lack of awareness not to dispose of batik waste in rivers. The findings of the study that the businessman batik Muslims in Pekalongan have the ethic of work are high and pass strategy development effort batik using principle business of Islam.